Detours of Trans-alpine Goods Transport by Road - Helmut Köll; Sandra Lange; Flavio V. Ruffini (Revue de Géographie Alpine)
Detours of trans-alpine freight transport by road are a constant issue on the traffic-policy agenda. A plethora of criteria regarding the definition of detours leads to diverging opinions prevailing in the individual Alpine countries and serves to complicate the discussion even further. This paper presents criteria regarding the definition of traffic detours as well as an analysis of the detours taken by heavy goods vehicles (trucks) at the Austrian and Swiss Alpine crossings in the year 2004. The analysis of routes taken goes to show that heavy goods vehicles do often not take the shortest routes. One point of interest is that only a few detours are taken via the St. Gotthard crossing. However, at the Brenner crossing, depending on the mode of computation, up to 740,000 of the 1,996,000 truck tours take a detour of more than 60 km via the Brenner crossing although 18.1% and 11.5% of all truck tours would have a shorter alternative route via the St. Gotthard and the San Bernardino crossing, respectively. A theoretical transfer of detours of more than 60 km to the shortest routes would lead to an increase in traffic of 38% at the St. Gotthard and 149% at the San Bernardino crossing. The amount of traffic at the Brenner and the Tauern crossing, on the other hand, would decrease by 31% and 16%, respectively.